Applications Artificial Intelligence (AI) and Machine Learning (ML) in the Mobile Banking Services Industry: A Bibliometric Review - Lukita Nova Azzara; M. Ruslianor Maika (Ekspektra (Online), 2025)
This study aims to explore the research on AI and ML Applications in Mobile Banking Industry Services conducted by previous researchers. Data was collected from the Scopus database using five keywords with the addition of terms and phrases, namely OR and AND according to the researcher's theme. The search results resulted in 283 publications on related issues. The data was analyzed using the VOS-Viewer and Biblioshiny applications in R-Studio. The results of the bibliometric analysis with biblioshiny describe the five categories identified by the researchers, namely: articles, sources, authors, institutions and countries described in each of the 10 most relevant images. Meanwhile, the results of bibliometric analysis with VOS-Viewer are described using Co-occurrence with item analysis of all keywords, which shows that Artificial Intelligence and Machine Learning citations are often used or encountered in research. So, the results of the study show an explanation that among the five categories, there are relationships with each other that have been identified, including the development of articles every year, which shows that in a period of 5 years, there has been a fairly rapid increase, especially in 2023-2024. There is the most dominant relevant source among other sources, namely Lecture Notes in Networks and Systems, connected with the most relevant institutions shown in Christ (Deemed To Be University), as well as showing scientific production in various countries, one of which is India, this can be a source of insight for new researchers in the growing future.